Shear-corrected Reissner-Mindlin plate model. (1st March 2019) - Freund, J.
Abstract: A new shear-corrected Reissner-Mindlin model is presented. The method reduces the modeling error of the classical model without affecting the form of the classical plate equations. Therefore, implementation on an existing software for the Reissner-Mindlin plate model is simple. The principle of virtual work and an explicit set of kinematic and kinetic assumptions is used in derivation. There, displacement assumption of the classical model is enhanced by a warping part which is eliminated to end up with equations for the classical part only. The equations differ from the classical ones in shear correction factors, modification in the source term, and stress expressions.